(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the pragmalinguistic features of connectives. The role of monologue speech is determined as an important factor in the manifestation of pragmalinguistic features of complex sentences, and the absence of pragmatic features of complex sentences in monologue speech is substantiated using examples.